An evolution model for the mobility of urban societal classes based on complex networks - Yi-Hua Zhou; Liang-Li Yang; Jieqi Lei; Rui-Jie Wu; Yi-Xiu Kong (Journal of Physics: Complexity)
Cities serve as the main platform for human socio-economic activities, where large crowds, products and information converge, forming complex societal interactions and the space for human to interact with each other. Like traditional geographical space, in cities, cyberspace and societal space also offer diverse channels for human interactions. While urban mobility in geographical space has been extensively studied across disciplines such as geography, economics, transportation and human behavior, mobility within societal space in cities has rarely been examined in depth. This paper focuses on the self-organized consolidation of mobility within urban societal spaces. Based on the rational actor assumption and Dunbar’s number, we construct a simple model to explain why urban societal classes spontaneously emerge in the evolution of societal space. We also find that the mobility within urban societal space decreases spontaneously over time and eventually outstanding individuals potentially can be trapped in lower classes, resulting in an inefficient matching of urban resources.